Debates About Cabinet Secrecy Are Far From Over - Cappe, Mel; Campagnolo, Yan (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2024)
In February 2024, the Supreme Court of Canada confirmed that Premier Doug Ford’s mandate letters to his ministers are protected by Cabinet secrecy and therefore exempt from the disclosure requirements of the provincial access to information regime. While this decision rightly recognized the importance of Cabinet secrecy to maintaining effective government, it raises concerns about the scope of this protection and its impact on the transparency and accountability of public institutions.